Pengaruh Edukasi Kelas Ibu Hamil Terhadap Kemampuan dalam Deteksi Dini Komplikasi Kehamilan di Wilayah Kerja Puskesmas Lendang Nangka Lombok Timur - Supiani; Wirastri, Dwi (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2023)
Pregnancy is a very vulnerable period, not only for pregnant women but also for the safety of the fetus in the womb. If pregnant women cannot recognize the danger signs of pregnancy early and detect them, it can result in morbidity and even death for the mother and fetus. In the January-August 2022 period, 254 (38.2%) of 664 pregnant women at Puskesmas Lendang Nangka experienced pregnancy complications. Objective: To determine the effect of class education on pregnant women on the ability to detect early complications of pregnancy in the Work Area of the Lendang Nangka Health Center in 2022. Methods: Quantitative research with a pre-experimental one group design pretest and posttest design. The population in this study were all pregnant women who attended classes for pregnant women in the Working Area of the Lendang Nangka Public Health Center from June to August 2022 with a total of 249 people. The number of samples in this study were 38 pregnant women. Sampling by means of purposive sampling. The collection of research data is a questionnaire that has been tested for validity and reliability. Data analysis used paired sample t-test. Results: There is an effect of class education on pregnant women on the ability to detect early complications of pregnancy in the Work Area of the Lendang Nangka Health Center in 2022, p value = 0.000 <0.05. Conclusion: Class education for pregnant women can affect the ability to perform early detection of pregnancy complications.